The method but not the protocol affects lactate-threshold determination in competitive swimmers - Arsoniadis, G. G.; Nikitakis, I. S.; Peyrebrune, M.; Botonis, P. G.; Toubekis, A. G. (International Journal of Sports Physiology and Performance, 2024)
Purpose The study validated variables corresponding to lactate threshold (LT) in swimming. Speed (sLT), blood lactate concentration (BLLT), oxygen uptake (VO2LT), and heart rate (HRLT) corresponding to LT were calculated by 2 different incremental protocols and validated in comparison with maximal lactate steady state (MLSS).